CONFLICT SITUATIONS ON DOUBLE-LANE ROUNDABOUT (Perner's Contacts, 2011)
The article presents the results of video analysis of conflict situations performed on double-lane roundabouts in Havířov-City. This paper was prepared with financial support for research and development project No. CG911-008-910 "Influence of structural elements geometry on safety and fluency of operation on roundabouts and possibility of rise crashes prediction”, the Ministry of Transport.
Keywords: Roundabout; Conflict Situation; road transport